36th Structures, Structural Dynamics and Materials Conference 1995
DOI: 10.2514/6.1995-1374
|View full text |Cite
|
Sign up to set email alerts
|

Simplified theory for contact indentation of sandwich panels

Abstract: Previous attempts to analyze indentation of sandwich panels have been based on small deflection theory and an assumed elastic core behaviour. The agreement with experiments was poor. The present work includes core crushing and large deflections of the face sheets in a simplified model of sandwich contact indentation. The model assumes transverse isotropy with respect to the load axis and is based on an infinite, elastic face sheet on a core bonded to a rigid foundation. The core is assumed to be elastic in ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…The motion of the projectile is governed by Newton's law and combining the equations of motion of the plate with that of the projectile we obtain the global set of second order differential equations The submatrices in Eqs (46,47) are the modal mass and stiffness matrices for modes i = 1,n and are given in Eq (43). M e is the mass of the projectile and where X represents the displacement of the projectile.…”
Section: P =P(t) 8(x-xo) 8(y-yo)mentioning
confidence: 99%
“…The motion of the projectile is governed by Newton's law and combining the equations of motion of the plate with that of the projectile we obtain the global set of second order differential equations The submatrices in Eqs (46,47) are the modal mass and stiffness matrices for modes i = 1,n and are given in Eq (43). M e is the mass of the projectile and where X represents the displacement of the projectile.…”
Section: P =P(t) 8(x-xo) 8(y-yo)mentioning
confidence: 99%
“…Thomsen [14] presented the results from a combined theoretical and experimental investigation of local bending effects in a clamped circular foam core sandwich plate subjected to a central point load, and a simple two-parameter elastic foundation model was used in order to include the shear interaction between the skin and core. Olsson and McManus [15] developed a simplified theory describing the contact indentation of sandwich plates based on a single-parameter foundation model for the core. Lee et al [16] investigated the impact dynamic response of composite sandwich plates impacted by a rigid ball.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, this model was sophisticated using the concept of linear elastic perfectly plastic foundation [9]. Olsson and McMannus [10] showed that the large deflection of plate theory, membrane theory, and core yielding significantly improve analytical predictions of the local load-indentation response of sandwich panels when compared to previous models assuming small deflection and elastic core response. But indentation analysis of the foam sandwich structures reinforced by fiber columns have not been addressed up to now.…”
Section: Introductionmentioning
confidence: 99%